Prototype Green Energy System for Real Estate Housing Development Based Internet of Everything - Suhendar Suhendar; Bambang Irawan; Gerry Firmansyah; Budi Tjahjono; Nixon Erzed; Mosiur Rahaman (Eduvest - Journal of Universal Studies, 2025)
Climate change and the crisis of conventional energy resources are two interrelated global issues that severely impact environmental sustainability and economic development. Real estate development using renewable energy is carried out for various reasons involving environmental, economic, and social aspects. Internet of Everything (IoE) is a concept that expands the Internet of Things (IoT), including machine-to-machine, machine-to-person, and person-to-person communications with expanded digital features. The research method is quantitative, with numerical data that can be statistically measured in system performance. The research focuses on developing a prototype architecture of green energy for real estate development to maximize the efficiency of solar energy potential. The research's conclusion holds excellent promise for broader implementation. Solar energy's efficiency and potential can be maximized as a renewable energy source by utilizing the Internet of Everything (IoE) for real-time monitoring, control, and analysis. Additionally, this approach can offer valuable insights for decision-making in energy management going forward.